2016
DOI: 10.1016/j.jgo.2016.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Designing exercise clinical trials for older adults with cancer: Recommendations from 2015 Cancer and Aging Research Group NCI U13 Meeting

Abstract: Cancer and its treatment can lead to a myriad of adverse events and negatively impact quality of life of older cancer patients and survivors. Unmet physical activity needs vary across the cancer continuum and remain an important yet understudied area of research in this population. Exercise interventions have been shown to be effective in treating both the physical and psychological declines associated with cancer and its treatment, with a potential to improve cancer-related outcomes. Despite the current evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(92 citation statements)
references
References 48 publications
1
90
0
1
Order By: Relevance
“…Several covariates that prior research identified as factors associated with participation of cancer survivors and older adults in PA were included: sex, race and ethnicity, marital status, educational levels, body mass index (BMI), comorbid illness, functional status (activities of daily living, instrumental activities of daily living), health status, insurance coverage, and access to medical care.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several covariates that prior research identified as factors associated with participation of cancer survivors and older adults in PA were included: sex, race and ethnicity, marital status, educational levels, body mass index (BMI), comorbid illness, functional status (activities of daily living, instrumental activities of daily living), health status, insurance coverage, and access to medical care.…”
Section: Methodsmentioning
confidence: 99%
“…There is scant research on PA levels in aging cancer survivors . Similar to the low PA levels in cancer survivors of all ages and older adults in general, PA levels of aging cancer survivors are expected to be low.…”
Section: Combined Summary Of Guidelines For Cancer Survivors and Oldementioning
confidence: 99%
“…We led a U13 grant (U13 AG038151), in close collaboration with the National Institute of Aging (NIA), the National Cancer Institute (NCI), and other major organizations (AGS, Gerontological Society of America, and the Alliance), which coordinated three research conferences composed of top leaders at the interface of aging and cancer research. The resulting series of 16 articles, including 4 major white papers, summarized the essential research priorities in geriatric oncology and identified that a coordinated research infrastructure and expertise to develop and prioritize these studies was desperately needed (Table ) . We also collaborated as principal investigators and coinvestigators on several other grants from the Patient‐Centered Outcomes Research Institute (PCORI), NCI, and NIA; hosted several conferences, bringing national leaders together; and coauthored dozens of other articles together.…”
Section: Carg: the Cancer And Aging Research Groupmentioning
confidence: 99%
“…The overarching mission of the conferences was: to provide a forum for a multidisciplinary team of investigators in geriatrics and oncology to review the present level of evidence in geriatric oncology, identify areas of highest research priority, and develop research approaches to improve clinical care for older adults with cancer within the next ten years. Seven SCOREboard members were funded by the U13 grant to attend the 2015 conference entitled “Design and Implementation of Intervention Studies to Maintain or Improve the Quality of Survival of Older and/or Frail Adults with Cancer” and served as coauthors on 7 articles . At this meeting, SCOREboard members also helped to guide future research priorities in the field of geriatric oncology.…”
Section: Introductionmentioning
confidence: 99%